2009
DOI: 10.1111/j.1467-839x.2008.01269.x
|View full text |Cite
|
Sign up to set email alerts
|

Sociopsychological profiles of students that leave the ingroup or engage in social competition

Abstract: We present a study of the sociopsychological profiles of students who are disposed to engage in social competition on behalf of ingroup interests. Five predictors were selected: the advantageous or unfavourable context for ingroup interests, group identification, meritocracy, just-world beliefs, and social dominance orientation. It was found that those students who were prepared to invest personal resources on behalf of ingroup interests were characterized by a strong group identification and middle or low sco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2015
2015

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…Thus, BJW is indicative of a personal contract (Lerner, ), which obliges individuals to behave fairly (cf. Echebarria‐Echabe, ). Previous research has found that individuals holding a strong BJW tend to endorse stronger social responsibility (Bierhoff, ) and obligation for reciprocity (Edlund, Sagarin & Johnson, ), are more likely to help people in need (Bierhoff, Klein & Kramp, ), and achieve their goals by just means than those holding weak BJW (e.g.…”
Section: Belief In a Just World And Rule‐breaking Behaviourmentioning
confidence: 99%
“…Thus, BJW is indicative of a personal contract (Lerner, ), which obliges individuals to behave fairly (cf. Echebarria‐Echabe, ). Previous research has found that individuals holding a strong BJW tend to endorse stronger social responsibility (Bierhoff, ) and obligation for reciprocity (Edlund, Sagarin & Johnson, ), are more likely to help people in need (Bierhoff, Klein & Kramp, ), and achieve their goals by just means than those holding weak BJW (e.g.…”
Section: Belief In a Just World And Rule‐breaking Behaviourmentioning
confidence: 99%
“…Meritocracy beliefs, although conceptually different from JWBs, are closely related. Meritocracy is the dominant legitimizing ideology of Western societies (Augoustinos, Tuffin, & Every, ; Echebarria, ; Gillies, ; Son Hing, Bobocel, & Zanna, ; Tajfel, ; Taylor & Moghaddam, ; Weber, ; Wright, Taylor, & Moghaddam, ). It assumes that social, political, and economic success depend on individual factors such as capacity, ambition, personal strength, and perseverance, rather than social factors such as gender, race, or class.…”
Section: System‐justifying Beliefs (Sjbs) Political Disaffection Anmentioning
confidence: 99%